Preparation method of multilayer composite SiO2 antireflection film

CN117331150BActive Publication Date: 2026-10-23SOUTHWEAT UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311496542.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-10
Publication Date
2026-10-23
Estimated Expiration
2043-11-10

AI Technical Summary

Technical Problem

SiO2增透膜因其制备简单、成膜高效、膜层牢固、增透效果好等优点而被广泛应用于增透膜研制工艺,但是单一SiO2增透膜材料参数优化空间有限,难以获得更高透过率,并且表面属于开孔结构,具有较强的吸湿性,导致其环境稳定性较差,从而损坏光纤通信系统中的光学元器件,减少其使用寿命;双层SiO2增透膜虽然能够获得较高的透过率,但透过率图谱为“Λ”型曲线,有效增透的波长范围较窄;例如申请号为202211335660.6的中国发明专利,公开了一种二氧化硅增透膜的制备方法,该申请公开了一种2~6层二氧化硅膜的制备方案,在具体实施例方案中,通过使用酸催化SiO2溶胶和碱催化SiO2溶胶混合作为底层膜A的原料,且酸催化SiO2溶胶和碱催化SiO2溶胶的体积比为1:4,使用HMDS/TEOS溶胶作为上层膜B的原料,然后将底层膜A和上层膜A提拉镀制得到双层二氧化硅增透膜,该双层二氧化硅增透膜的高透光率波段集中在中心波长351nm、527nm、1053nm、1064nm处,因而该双层二氧化硅增透膜不具备对红外波长范围光的高透过率

Benefits of technology

[0021]本发明至少包括以下有益效果:本发明首先采用溶胶-凝胶法制备酸催化SiO2溶胶和碱催化SiO2溶胶,利用PEC-6型等离子体清洗机对基底进行清洗,通过提拉法对两种溶胶进行复合镀制,制备了透过率高、表面质量高、环境稳定性好的A/A/B/B四层复合SiO2增透膜,该增透膜在1300nm~1600nm红外波长范围内透光率>99%,反射率<0.5%;具有良好的疏水性,水接触角达到了≥125°;粗糙度较低,表面平整度高。这种多层复合SiO2增透膜在1300nm~1600nm红外波长范围内的各项性能指标均优于传统单层或双层SiO2增透膜,也优于传统四层增透膜,适用于光纤通信领域中的光纤连接器、波分复用器等光通信元器件,同时也可广泛应用于军事、大气探测、航空航天等红外光学领域。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117331150B_ABST
    Figure CN117331150B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a multilayer composite SiO2 antireflection film, which comprises the following steps: preparing an A / A / B / B four-layer SiO2 film by a sol-gel pulling film method, wherein A is prepared by mixing acid-catalyzed SiO2 sol and base-catalyzed SiO2 sol, the volume ratio of the base-catalyzed SiO2 sol and the acid-catalyzed SiO2 sol is 1:9, B is prepared by HMDT-treated HSNs sol, and the A / A / B / B four-layer pulling and stacking sequence realizes a strong antireflection effect in a wide spectral range. The four-layer composite SiO2 antireflection film prepared by the method has all performance indexes in the infrared wavelength range of 1300 nm to 1600 nm superior to those of traditional single-layer, double-layer or four-layer SiO2 antireflection films, and is suitable for optical fiber connectors, wavelength division multiplexers and other optical communication components in the field of optical fiber communication, and can also be widely applied to the fields of infrared optics such as military, atmospheric detection, aerospace and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of optical technology, and more specifically, this invention relates to a method for preparing a multilayer composite SiO2 antireflection film. Background Technology

[0002] Infrared technology was initially used primarily in the military field. Later, with the development of technology, it gradually played an important role in civilian fields such as atmospheric detection, aerospace, and aviation. More and more optical devices are required to operate in the infrared band. In infrared optical systems, the transmittance of infrared light energy determines the performance of the system; reducing reflection from the surface of optical components and increasing the transmittance of the optical system within its operating band is of great significance for practical production. Optical fiber communication mainly uses light in the infrared region, typically in the wavelength range of 800nm ​​to 1600nm, with 1310nm and 1550nm being the most commonly used wavelengths. However, due to high fiber loss and reflection in optical fiber communication systems, signal attenuation occurs during transmission, affecting the effective distance and volume of data transmission. Therefore, it is necessary to deposit antireflection coatings with broad-spectrum, high transmittance in the infrared wavelength range on the surfaces of optical fiber connectors, wavelength division multiplexers, and other optical fiber communication components. Simultaneously, due to the variability of the optical fiber communication application environment, the antireflection coating also needs good environmental stability. Therefore, it is necessary to design antireflection coatings with high transmittance in the 1310nm–1550nm infrared wavelength range. SiO2 antireflection films are widely used in antireflection film manufacturing processes due to their advantages such as simple preparation, high efficiency in film formation, strong film layer, and good antireflection effect. However, the optimization space for material parameters of single SiO2 antireflection films is limited, making it difficult to obtain higher transmittance. Furthermore, the surface has an open-pore structure and strong hygroscopicity, resulting in poor environmental stability, which can damage optical components in fiber optic communication systems and reduce their service life. Although double-layer SiO2 antireflection films can achieve higher transmittance, the transmittance spectrum is a "Λ"-shaped curve, indicating a narrow effective wavelength range for antireflection. For example, Chinese invention patent application number 202211335660.6 discloses a method for preparing a silica antireflection film. This application discloses a preparation scheme for a 2-6 layer silica film. In a specific embodiment, an acid-catalyzed SiO2 sol and an alkali-catalyzed SiO2 sol are mixed as the raw material for the bottom film A, with a volume ratio of 1:4. HMDS / TEOS sol is used as the raw material for the top film B. Then, the bottom film A and the top film A are dip-coated to obtain a double-layer silica antireflection film. The high transmittance band of this double-layer silica antireflection film is concentrated at the center wavelengths of 351nm, 527nm, 1053nm, and 1064nm. Therefore, this double-layer silica antireflection film does not have high transmittance for infrared wavelengths. Therefore, to meet the requirement of high transmittance in the 1310nm-1550nm infrared wavelength range, it is necessary to prepare a multilayer composite SiO2 antireflection film with high transmittance, high surface quality, and good environmental stability. Summary of the Invention

[0003] One object of the present invention is to solve at least the above-mentioned problems and / or defects, and to provide at least the advantages described below.

[0004] To achieve these objectives and other advantages according to the present invention, a method for preparing a multilayer composite SiO2 antireflection film is provided, comprising:

[0005] A four-layer SiO2 film (A / A / B / B) was prepared by sol-gel dip coating. A was prepared by mixing acid-catalyzed SiO2 sol and alkali-catalyzed SiO2 sol with a volume ratio of 1:9. B was prepared by HMDS-treated HSNs sol. The four layers were dip-coated in sequence to achieve a strong anti-reflection effect over a wide spectral range.

[0006] Preferably, the process specifically includes the following steps:

[0007] Step 1: Preparation of alkaline-catalyzed SiO2 sol. The specific method is as follows: Take an appropriate amount of tetraethyl orthosilicate, anhydrous ethanol, deionized water and ammonia water and mix them to obtain a solution. Seal the solution in a reactor and stir it magnetically for a certain time under a certain temperature condition. Then place it at room temperature for a certain time to age and obtain alkaline-catalyzed SiO2 sol.

[0008] Step 2: Preparation of acid-catalyzed SiO2 sol. The specific method is as follows: Take an appropriate amount of tetraethyl orthosilicate, anhydrous ethanol and deionized water and mix them evenly. The deionized water contains a certain amount of concentrated hydrochloric acid to obtain a reaction solution. Seal the reaction solution in a reactor and stir it for a certain time under a certain temperature. Then place it at room temperature for a certain time to age to obtain acid-catalyzed SiO2 sol.

[0009] Step 3: Reflux and condense the alkali-catalyzed SiO2 sol for a certain period of time to remove ammonia, and then filter it with polytetrafluoroethylene filter paper. Then mix the alkali-catalyzed SiO2 sol and the acid-catalyzed SiO2 sol at a volume ratio of 1:9 to obtain an acid-base composite sol, which is denoted as sol 1.

[0010] Step 4: Treat HSNs sol with HMDS. The specific method is as follows: Dissolve an appropriate amount of polyacrylic acid in ammonia water, and then add it to anhydrous ethanol to obtain a reaction solution. Next, divide tetraethyl orthosilicate into five equal parts and add them to the reaction solution. The addition of each part of tetraethyl orthosilicate is set at a certain time interval, and the mixture is stirred continuously during the process. Finally, add hexamethyldisilazane and age the mixture to obtain HMDS-treated HSNs sol, which is denoted as sol 2.

[0011] Step 5: Place the substrate into a PCE-6 plasma cleaner for plasma cleaning;

[0012] Step 6: Place the plasma-cleaned substrate into an ethanol solution for ultrasonic cleaning, followed by blowing and drying.

[0013] Step 7: First, immerse the dried substrate in sol 1, and then deposit the first film A on the substrate surface at a certain pulling speed; then deposit another film A on the first film A at the same speed; then immerse the substrate with two films A on it in sol 2 for a certain time, and then deposit the third film B on the surface of the second film A at a certain pulling speed; then immerse the substrate with the third film B on it in sol 1 for a certain time, and then deposit the fourth film B on the surface of the third film B at a certain pulling speed, thus obtaining a four-layer composite SiO2 antireflection film.

[0014] Preferably, in step one, the volume ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water and ammonia is 1:10:0.5:0.3, the stirring temperature is 50°C, the magnetic stirring time is 6 hours, and the aging time at room temperature is 48 hours.

[0015] Preferably, in step two, the volume ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water, and concentrated hydrochloric acid is 1:10:0.4:0.02, the stirring temperature is 50°C, the stirring time is 6 hours, and the mixture is aged at room temperature for 48 hours.

[0016] Preferably, in step three, the reflux condensation time of the alkali-catalyzed SiO2 sol is 6 hours, the reflux condensation temperature is 90°C, the pore size of the straightened polytetrafluoroethylene is 0.22 μm, and the filtration pressure is 0.09 MPa.

[0017] Preferably, in step four, the mass-to-volume ratio of polyacrylic acid, ammonia, tetraethyl orthosilicate, anhydrous ethanol, and hexamethyldisilazane is 0.06–0.08 g: 6–8 mL: 180 mL: 1 mL: 10 mL. Tetraethyl orthosilicate is added in five portions, with an interval of 1 hour between each addition. The mixture is stirred at room temperature for 6 hours, and finally hexamethyldisilazane is added. The aging time is 48 hours.

[0018] Preferably, in step five, the cleaning power of the PCE-6 plasma cleaner placed on the substrate is 10W.

[0019] Preferably, step seven specifically includes: first immersing the dried substrate in sol 1 for 1 minute, then depositing a first film A on the substrate surface at a pulling speed of 100 mm / min; then depositing another film A on the first film A at the same speed; then immersing the substrate with two films A on sol 2 for 30 seconds, then depositing a third film B on the surface of the second film A at a pulling speed of 80 mm / min; then immersing the substrate with the third film B on sol 1 for 30 seconds, then depositing a fourth film B on the surface of the third film B at the same pulling speed, thus obtaining an A / A / B / B four-layer composite SiO2 antireflection film.

[0020] An application of a multilayer composite SiO2 antireflection film is disclosed. This multilayer composite SiO2 antireflection film is used in infrared optical systems, including fiber optic connectors and wavelength division multiplexers. The film exhibits a transmittance >99% and a reflectance <0.5% in the 1300nm–1600nm infrared wavelength range, and a water contact angle ≥125°.

[0021] This invention offers at least the following advantages: Firstly, acid-catalyzed SiO2 sol and alkali-catalyzed SiO2 sol are prepared using the sol-gel method. The substrate is cleaned using a PEC-6 plasma cleaner. Then, the two sols are compositely deposited using a dip-coating method to prepare a four-layer composite SiO2 antireflection film (A / A / B / B) with high transmittance, high surface quality, and good environmental stability. This antireflection film exhibits a transmittance >99% and a reflectance <0.5% in the 1300nm–1600nm infrared wavelength range. It also possesses good hydrophobicity, with a water contact angle ≥125°, low roughness, and high surface smoothness. This multilayer composite SiO2 antireflection film outperforms traditional single-layer or double-layer SiO2 antireflection films, and is also superior to traditional four-layer antireflection films, in the 1300nm–1600nm infrared wavelength range. It is suitable for optical communication components such as fiber optic connectors and wavelength division multiplexers in the field of optical fiber communication, and can also be widely applied in infrared optics fields such as military, atmospheric detection, and aerospace.

[0022] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Attached Figure Description

[0023] Figure 1 The transmittance diagram is shown for the A / A / B / B four-layer composite SiO2 antireflection membrane prepared in Example 1 of this invention.

[0024] Figure 2 The reflectance diagram of the A / A / B / B four-layer composite SiO2 antireflection film prepared in Example 1 of this invention;

[0025] Figure 3 The transmittance diagram shows the A / A / B / B four-layer composite SiO2 antireflection membrane prepared in Comparative Example 1 of this invention.

[0026] Figure 4 The reflectance diagram shows the A / B / A / B four-layer composite SiO2 antireflection film prepared in Comparative Example 1 of this invention.

[0027] Figure 5 The transmittance diagram shows the A / B / A / B four-layer composite SiO2 antireflection membrane prepared in Comparative Example 2 of this invention.

[0028] Figure 6 The reflectance diagram is shown for the A / B / A / B four-layer composite SiO2 antireflection film prepared in Comparative Example 2 of this invention.

[0029] Figure 7 The image shows the AFM pattern of the A / B / A / B four-layer composite SiO2 antireflection film prepared in Example 1 of this invention.

[0030] Figure 8 The contact angle diagram is shown for the A / B / A / B four-layer composite SiO2 antireflection film prepared in Example 1 of this invention. Detailed Implementation

[0031] The present invention will now be described in further detail with reference to the accompanying drawings, so that those skilled in the art can implement it based on the description.

[0032] It should be understood that terms such as “having,” “comprising,” and “including” as used herein do not exclude the presence or addition of one or more other elements or combinations thereof.

[0033] Example 1

[0034] This embodiment provides a method for preparing an A / A / B / B four-layer composite SiO2 antireflection film, including the following steps:

[0035] Step 1: Preparation of alkaline-catalyzed SiO2 sol. The specific method is as follows: Take 5 mL of tetraethyl orthosilicate, 50 mL of anhydrous ethanol, 2.5 mL of deionized water and 1.5 mL of ammonia water and mix them to obtain a solution. Seal the solution in a reactor and stir it magnetically at 50°C for 6 h. Then place it at room temperature for aging for 48 h to obtain alkaline-catalyzed SiO2 sol.

[0036] Step 2: Preparation of acid-catalyzed SiO2 sol. The specific method is as follows: Take 5 mL of tetraethyl orthosilicate, 50 mL of anhydrous ethanol and 2 mL of deionized water and mix them evenly. The deionized water contains 0.1 mL of concentrated hydrochloric acid to obtain a reaction solution. Seal the reaction solution in a reactor and stir it at 50°C for 6 h. Then place it at room temperature for 48 h to age it to obtain acid-catalyzed SiO2 sol.

[0037] Step 3: The alkaline-catalyzed SiO2 sol was refluxed and condensed at 90°C for 6 hours to remove ammonia. Then, it was filtered with 0.22μm polytetrafluoroethylene filter paper at a vacuum pressure of 0.09MPa. The filtered alkaline-catalyzed SiO2 sol and acid-catalyzed SiO2 sol were mixed at a volume ratio of 1:9 to obtain an acid-base composite sol, which is denoted as sol 1.

[0038] Step 4: Treat the HSNs sol with HMDS. The specific method is as follows: First, dissolve 0.06g of polyacrylic acid in 7mL of ammonia water, and then add it to 180mL of anhydrous ethanol. Next, divide 1.0mL of TEOS into five equal portions and add them to the above reaction solution at 1-hour intervals. Stir continuously for 6 hours during this period. Finally, add 10mL of hexamethyldisilazane (HMDS) to the above sol and age for 48 hours to obtain the HMDS-treated HSNs sol, which is designated as sol 2.

[0039] Step 5: Place the substrate into a PCE-6 plasma cleaner for plasma cleaning at a power of 10W to improve the cleanliness of the substrate and the water-repellency of the film surface.

[0040] Step 6: Place the plasma-cleaned substrate into an ethanol solution for ultrasonic cleaning and then dry it by blowing.

[0041] Step 7: First, immerse the dried substrate in sol 1 for 1 minute, then deposit the first film A on the substrate surface at a pulling speed of 100 mm / min; then deposit another film A at a speed of 80 mm / min. Next, immerse the substrate with two layers of film A in sol 2 for 30 seconds, then deposit the third film B on the surface of the two layers of film A at a pulling speed of 100 mm / min; finally, deposit the fourth film B at a speed of 80 mm / min, thus obtaining the A / A / B / B four-layer composite antireflection film.

[0042] The four-layer composite SiO2 antireflective film sample prepared in Example 1 was measured using a UV spectrophotometer, atomic force microscope, and water contact meter. The transmittance of the four-layer composite SiO2 antireflective film sample at the center wavelength of 1200 nm to 1500 nm was found to be greater than 99%. Figure 1 As shown; Figure 2 As shown, the reflectivity for light in the wavelength range of 900nm to 1800nm ​​can be less than 0.5%; for example... Figure 7 As shown, the surface roughness RMS is 1.53 nm; Figure 8 As shown, the water contact angle is 125.99°.

[0043] Comparative Example 1

[0044] This embodiment provides a method for preparing an A / A / B / B four-layer composite SiO2 antireflection film, including the following steps:

[0045] Step 1: Preparation of alkaline-catalyzed SiO2 sol. The specific method is as follows: Take 5 mL of tetraethyl orthosilicate, 50 mL of anhydrous ethanol, 2.5 mL of deionized water and 1.5 mL of ammonia water and mix them to obtain a solution. Seal the solution in a 250 mL double-necked round-bottom flask and stir it magnetically at 50 °C for 6 h. Then place it at room temperature for aging for 48 h to obtain alkaline-catalyzed SiO2 sol.

[0046] Step 2: Preparation of acid-catalyzed SiO2 sol. The specific method is as follows: Take 5 mL of tetraethyl orthosilicate, 50 mL of anhydrous ethanol and 2 mL of deionized water and mix them evenly. The deionized water contains 0.1 mL of concentrated hydrochloric acid to obtain a reaction solution. Seal the reaction solution in a reactor and stir it at 50°C for 6 h. Then place it at room temperature for 48 h to age it to obtain acid-catalyzed SiO2 sol.

[0047] Step 3: The alkaline-catalyzed SiO2 sol was refluxed and condensed at 90°C for 6 hours to remove ammonia. Then, it was filtered with 0.22μm polytetrafluoroethylene filter paper at a vacuum pressure of 0.09MPa. The filtered alkaline-catalyzed SiO2 sol and acid-catalyzed SiO2 sol were mixed at a volume ratio of 1:9 to obtain an acid-base composite sol, which is denoted as sol 1.

[0048] Step 4: Prepare HMDS / TEOS sol. The specific method is as follows: Mix 50 ml of anhydrous ethanol, 0.5 ml of ammonia, 1.5 ml of deionized water, 0.5 ml of hexamethyldisilazane, and 5 ml of tetraethyl orthosilicate. Add these reagents to the reactor and stir at 50°C for 6 hours. Then, let it age at room temperature for 48 hours. Add anhydrous ethanol that accounts for 50% of the total volume of anhydrous ethanol, ammonia, deionized water, hexamethyldisilazane, and tetraethyl orthosilicate to obtain HMDS / TEOS sol, which is denoted as sol 2.

[0049] Step 5: Place the substrate into a PCE-6 plasma cleaner for plasma cleaning at a power of 10W to improve the cleanliness of the substrate and the water-repellency of the film surface.

[0050] Step 6: Place the plasma-cleaned substrate into an ethanol solution for ultrasonic cleaning and then dry it by blowing.

[0051] Step 7: First, immerse the dried substrate in sol 1 for 1 minute, then deposit the first film A on the substrate surface at a pulling speed of 100 mm / min; then deposit another film A on the first film A at the same speed; then immerse the substrate with two films A on sol 2 for 30 seconds, then deposit the third film B on the surface of the second film A at a pulling speed of 80 mm / min; then immerse the substrate with the third film B on sol 1 for 30 seconds, then deposit the fourth film B on the surface of the third film B at the same pulling speed, thus obtaining the A / A / B / B four-layer composite SiO2 antireflection film.

[0052] like Figure 3 and Figure 4 As shown, the A / A / B / B four-layer composite SiO2 antireflection film prepared in this embodiment has a transmittance of 99.32% at a center wavelength of 130nm, but the wavelength range with transmittance greater than 99% is significantly smaller than that of the A / A / B / B four-layer composite SiO2 antireflection film in Example 1. Although the minimum reflectance is 0.48%, the range with reflectance less than 0.5% is also significantly smaller than that of Example 1.

[0053] Comparative Example 2

[0054] This embodiment provides a method for preparing an A / B / A / B four-layer composite SiO2 antireflection film, including the following steps:

[0055] Step 1: Preparation of alkaline-catalyzed SiO2 sol. The specific method is as follows: Take 5 ml of tetraethyl orthosilicate, 50 ml of anhydrous ethanol and 1.5 ml of ammonia water and mix them to obtain a solution. Seal the solution in a reactor and stir it magnetically for 6 h at 50 °C. Then place it at room temperature for aging for 48 h to obtain alkaline-catalyzed SiO2 sol.

[0056] Step 2: Preparation of acid-catalyzed SiO2 sol. The specific method is as follows: Take 5 ml of tetraethyl orthosilicate, 50 ml of anhydrous ethanol and 2 ml of deionized water and mix them evenly. The deionized water contains 0.1 ml of concentrated hydrochloric acid to obtain a reaction solution. Seal the reaction solution in a reactor and stir it at 50°C for 6 h. Then place it at room temperature for 48 h to age it to obtain acid-catalyzed SiO2 sol.

[0057] Step 3: Reflux and condense the alkali-catalyzed SiO2 sol at 90°C for 6 hours to remove ammonia. Then, mix the alkali-catalyzed SiO2 sol and the acid-catalyzed SiO2 sol at a volume ratio of 1:9 to obtain an acid-base composite sol, denoted as sol 1.

[0058] Step 4: Prepare HMDS / TEOS sol. The specific method is as follows: Mix 50 ml of anhydrous ethanol, 0.5 ml of ammonia, 1.5 ml of deionized water, 0.5 ml of hexamethyldisilazane, and 5 ml of tetraethyl orthosilicate. Add these reagents to the reactor and stir at 50°C for 6 hours. Then, let it age at room temperature for 48 hours. Add anhydrous ethanol that accounts for 50% of the total volume of anhydrous ethanol, ammonia, deionized water, hexamethyldisilazane, and tetraethyl orthosilicate to obtain HMDS / TEOS sol, which is denoted as sol 2.

[0059] Step 5: Place the substrate into a PCE-6 plasma cleaner for plasma cleaning at a power of 10W to improve the cleanliness of the substrate and the water-repellency of the film surface.

[0060] Step 6: Place the plasma-cleaned substrate into an ethanol solution for ultrasonic cleaning and then dry it by blowing.

[0061] Step 7: First, immerse the dried substrate in sol 1 for 1 minute, then deposit the first film A on the substrate surface at a pulling speed of 100 mm / min; then immerse the substrate with the first film A in sol 2 for 1 minute, then deposit the second film B on the surface of the first film A at a pulling speed of 80 mm / min; then immerse the substrate with the second film B in sol 1 for 30 seconds, then deposit the third film A on the surface of the second film B at a pulling speed of 100 mm / min; finally, immerse the substrate with the third film A in sol 2 for 30 seconds, then deposit the fourth film B on the surface of the third film A at a pulling speed of 80 mm / min, thus obtaining the A / B / A / B four-layer composite SiO2 antireflection film.

[0062] The four-layer composite SiO2 antireflection film sample A / B / A / B prepared in Comparative Example 2 was measured using a UV spectrophotometer, atomic force microscope, and water contact meter. The transmittance of the four-layer composite SiO2 antireflection film sample at a center wavelength of 1500 nm was 99.21%, but the wavelength range with transmittance greater than 99% was also lower than that of the four-layer A / A / B / B antireflection film prepared in Example 1. Figure 5 As shown; Figure 6 As shown, the lowest reflectance is only 0.68%, which is significantly lower than that of the A / A / B / B four-layer antireflection film prepared in Example 1.

[0063] The number of devices and processing scale described herein are for the purpose of simplifying the description of the invention. Applications, modifications, and variations of the invention will be readily apparent to those skilled in the art.

[0064] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.

Claims

1. A method for preparing a multilayer composite SiO2 antireflection film, characterized in that, include: A four-layer SiO2 film (A / A / B / B) was prepared by sol-gel dip coating. A was prepared by mixing acid-catalyzed SiO2 sol and alkali-catalyzed SiO2 sol with a volume ratio of 1:

9. B was prepared by HMDS-treated HSNs sol. The four-layer dip coating of A / A / B / B achieved a strong anti-reflection effect over a wide spectral range. Specifically, the following steps are included: Step 1: Preparation of alkaline-catalyzed SiO2 sol. The specific method is as follows: Take an appropriate amount of tetraethyl orthosilicate, anhydrous ethanol, deionized water and ammonia water and mix them to obtain a solution. Seal the solution in a reactor and stir it magnetically for a certain time under a certain temperature condition. Then place it at room temperature for a certain time to age and obtain alkaline-catalyzed SiO2 sol. Step 2: Preparation of acid-catalyzed SiO2 sol. The specific method is as follows: Take an appropriate amount of tetraethyl orthosilicate, anhydrous ethanol and deionized water and mix them evenly. The deionized water contains a certain amount of concentrated hydrochloric acid to obtain a reaction solution. Seal the reaction solution in a reactor and stir it for a certain time under a certain temperature. Then place it at room temperature for a certain time to age to obtain acid-catalyzed SiO2 sol. Step 3: Reflux and condense the alkali-catalyzed SiO2 sol for a certain period of time to remove ammonia, and then filter it with polytetrafluoroethylene filter paper. Then mix the alkali-catalyzed SiO2 sol and the acid-catalyzed SiO2 sol at a volume ratio of 1:9 to obtain an acid-base composite sol, which is denoted as sol 1. Step 4: Treat HSNs sol with HMDS. The specific method is as follows: Dissolve an appropriate amount of polyacrylic acid in ammonia water, and then add it to anhydrous ethanol to obtain a reaction solution. Next, divide tetraethyl orthosilicate into five equal parts and add them to the reaction solution. The addition of each part of tetraethyl orthosilicate is set at a certain time interval, and the mixture is stirred continuously during the process. Finally, add hexamethyldisilazane and age the mixture to obtain HMDS-treated HSNs sol, which is denoted as sol 2. Step 5: Place the substrate into a PCE-6 plasma cleaner for plasma cleaning; Step 6: Place the plasma-cleaned substrate into an ethanol solution for ultrasonic cleaning and then dry it by blowing. Step 7: First, immerse the dried substrate in sol 1, then deposit the first film A on the substrate surface at a pulling speed of 100 mm / min; then deposit another film A on the first film A at a speed of 80 mm / min; then immerse the substrate with two film A layers in sol 2 for a certain time, then deposit the third film B on the surface of the second film A at a pulling speed of 100 mm / min; then immerse the substrate with the third film B in sol 2 for a certain time, then deposit the fourth film B on the surface of the third film B at a pulling speed of 80 mm / min, thus obtaining a four-layer composite SiO2 antireflection film; In step four, the mass-to-volume ratio of polyacrylic acid, ammonia, tetraethyl orthosilicate, anhydrous ethanol, and hexamethyldisilazane is 0.06~0.08g:6~8mL:180mL:1mL:10mL. Tetraethyl orthosilicate is added in five portions, with an interval of 1 hour between each addition. The mixture is stirred at room temperature for 6 hours, and finally hexamethyldisilazane is added. The aging time is 48 hours.

2. The method for preparing the multilayer composite SiO2 antireflection film as described in claim 1, characterized in that, In step one, the volume ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water and ammonia is 1:10:0.5:0.3, the stirring temperature is 50 ℃, the magnetic stirring time is 6 h, and the aging time at room temperature is 48 h.

3. The method for preparing the multilayer composite SiO2 antireflection film as described in claim 1, characterized in that, In step two, the volume ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water, and concentrated hydrochloric acid is 1:10:0.4:0.02, the stirring temperature is 50 ℃, the stirring time is 6 h, and the mixture is aged at room temperature for 48 h.

4. The method for preparing the multilayer composite SiO2 antireflection film as described in claim 1, characterized in that, In step three, the reflux condensation time of the alkali-catalyzed SiO2 sol is 6 h, and the reflux condensation temperature is 90 ℃; the pore size of the polytetrafluoroethylene filter paper is 0.22 μm, and the filtration pressure is 0.09 MPa.

5. The method for preparing the multilayer composite SiO2 antireflection film as described in claim 1, characterized in that, In step five, the substrate is placed in a PCE-6 plasma cleaner with a cleaning power of 10 W.

6. The application of a multilayer composite SiO2 antireflection membrane prepared by the method according to any one of claims 1-5, characterized in that, The multilayer composite SiO2 antireflective film is applied in infrared optical systems, including fiber optic connectors and wavelength division multiplexers. The multilayer composite SiO2 antireflective film has a transmittance of >99% and a reflectance of <0.5% in the infrared wavelength range of 1300 nm to 1600 nm, and a water contact angle of ≥125°.

Citation Information

Patent Citations

  • Preparation method of SiO2 anti-reflection film with ultralow refractive index

    CN109665720A

  • Preparation method of silicon dioxide antireflection film

    CN115555235A